Price-setting behaviour in Belgium: what can be learned from an ad hoc survey? - Luc Aucremanne; Martine Druant (European Central Bank (ECB), 2005)
This paper reports the results of an ad hoc survey on price-setting behaviour conducted in February 2004 among 2,000 Belgian firms. The reported results clearly deviate from a situation of perfect competition and show that firms have some market power. Pricing-to-market is applied by a majority of industrial firms. Prices are rather sticky. The average duration between two consecutive price reviews is 10 months, whereas it amounts to 13 months between two consecutive price changes. Most firms adopt time-dependent price reviewing under normal circumstances. However, when specific events occur, the majority will adopt a state-dependent behaviour. Evidence is found in favour of both nominal (mainly implicit and explicit contracts) and real rigidities (including flat marginal costs and counter-cyclical movements in desired mark-ups). The survey results point to a non-negligible degree of non-optimal price-setting.
Keywords: D40; E31; L11; 330; nominal rigidity; price rigidity; price-setting behaviour; pricing-to-market; real rigidity; state-dependent pricing; survey; timedependent pricing; Preismanagement; Marktmacht; Preisrigidität; Belgien